Change in conjugated even-even molybdenum, isotopes, in different energy states - Emad Ahmed; ruaa alnaema (College of Education for Pure Sciences, 2012)
ABSTACTS The properties of the different states of even-even isotopes have been established. The examination of the energy of state and the ratio for these isotopes show that the isotope has a vibration property but the others have -unstable property as approached from the rotation property. Drawing as a function of for these isotopes showed a variation of their property, and to confirm these variation the suitable equations for each limit have been used to calculate the energy of different states of these isotopes. The interacting boson model has been applied to calculate the energy of different states and a comparison with the experimental data showed good agreements.